Hypercalcemia associated with cosmetic injections: a systematic review. Issue 4 (April 2018) - Tachamo, Niranjan; Donato, Anthony; Timilsina, Bidhya; Nazir, Salik; Lohani, Saroj; Dhital, Rashmi; Basnet, Sijan
Abstract : Introduction: Cosmetic injections with silicone and polymethylmethacrylate are not FDA approved for augmentation of body parts such as breast, buttock or legs, but they have been widely used for decades. Cosmetic injections can cause foreign body granulomas and occasionally severe and life-threatening hypercalcemia. We aimed to systematically analyze the published literature on cosmetic injection-associated hypercalcemia. Methods: We searched relevant articles on hypercalcemia associated with various cosmetic injections and extracted relevant data on demographics, cosmetic injections used, severity of hypercalcemia, management and outcomes. Results: We identified 23 eligible patients from 20 articles. Mean age was 49.83 ± 14.70 years with a female preponderance (78.26% including transgender females). Silicone was most commonly used, followed by polymethylmethacrylate and paraffin oil (43.48, 30.43, and 8.70% respectively). The buttock was the most common site followed by the breast (69.57% and 39.13% respectively). Hypercalcemia developed at mean duration of 7.96 ± 7.19 years from the initial procedure. Mean ionized calcium at presentation was 2.19 ± 0.61 mmol/L and mean corrected calcium at presentation was 3.43 ± 0.31 mmol/L. 1, 25-Dihydroxyvitamin D (1, 25(OH)2 D or calcitriol) was elevated while 25-hydroxyvitamin D (25(OH)D) and PTH were low in majority of cases. Hypercalcemia was managed conservatively with hydration, corticosteroids and bisphosphonates in majority of cases. Surgery was attempted in 2 cases but was unsuccessful. Renal failure was the most common complication (82.35% cases) and 2 patients died. Conclusion: Hypercalcemia from cosmetic injections can be severe and life threatening and can present years after the initial procedure. Cosmetic injection-associated granuloma should be considered a cause of hypercalcemia, especially in middle-aged females presenting with non-PTH-mediated, non-malignant hypercalcemia, which is often associated with elevated calcitriol; however, it should be noted that calcitriol level may be normal as well.